Does the Rural Environment Influence Symptomatology and Optimize the Effectiveness of Disease Acceptance? A Study Among Women With Fibromyalgia - Catalá, Patricia; Blanco, Sheila; Perez-Calvo, Soledad; Luque-Reca, Octavio; Bedmar, Dolores; Peñacoba, Cecilia (Frontiers in Psychology, 2021)
The present study aims to explore whether the symptoms associated with fibromyalgia are really contextually determined by the area of residence (rural / urban). Furthermore, it is analyzed whether the effect of the acceptance of the disease on the emotional, cognitive and physical symptoms is moderated by the patients’ place of residence. Using a cross-sectional design, a total of 234 women with fibromyalgia (mean age = 56.91 years; SD = 8.94) were surveyed, of which 55.13% resided in rural areas and 44.87% in urban areas. Self-reported questionnaires were used to assess pain severity, anxiety and depression, functional limitation, physical and mental fatigue and acceptance of the disease. The results show significant differences in acceptance (p = .040), pain (p < .001), and physical and mental fatigue (p =.003 and p = .004, respectively) between patients from rural and urban areas. The rural area patients presented higher levels of acceptance and pain and lesser levels of physical and mental fatigue compared to the urban area. The moderation analyzes add that the variables of physical symptoms (pain, functional limitation and physical fatigue) were significantly and negatively associated with acceptance, only in patients from the rural area. This study addresses for the first time the role of the place of residence in suffering from fibromyalgia, suggesting that the rural or urban environment plays a relevant role in the appearance, maintenance and / or severity of symptoms in fibromyalgia women. Limitations and practical implications are also discussed.